2007
DOI: 10.1074/jbc.m703434200
|View full text |Cite
|
Sign up to set email alerts
|

Stabilization of Hyperdynamic Microtubules Is Neuroprotective in Amyotrophic Lateral Sclerosis

Abstract: Mutations in copper/zinc superoxide dismutase 1 (SOD1), a genetic cause of human amyotrophic lateral sclerosis, trigger motoneuron death through unknown toxic mechanisms. We report that transgenic SOD1G93A mice exhibit striking and progressive changes in neuronal microtubule dynamics from an early age, associated with impaired axonal transport. Pharmacologic administration of a microtubule-modulating agent alone or in combination with a neuroprotective drug to symptomatic SOD1G93A mice reduced microtubule turn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
100
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 96 publications
(103 citation statements)
references
References 46 publications
3
100
0
Order By: Relevance
“…The binding of SOD1 G93A to mitochondria (25) may also reduce ATP production, thereby reducing its availability for dyneinmediated transport. This defect may be worsened by the accumulation of hyperdynamic microtubules in presymptomatic SOD1 G93A mice (42). This hypothesis is supported by our work showing deficits in the bidirectional transport of mitochondria in vivo in SOD1 G93A mice at a presymptomatic stage.…”
Section: Discussionsupporting
confidence: 78%
“…The binding of SOD1 G93A to mitochondria (25) may also reduce ATP production, thereby reducing its availability for dyneinmediated transport. This defect may be worsened by the accumulation of hyperdynamic microtubules in presymptomatic SOD1 G93A mice (42). This hypothesis is supported by our work showing deficits in the bidirectional transport of mitochondria in vivo in SOD1 G93A mice at a presymptomatic stage.…”
Section: Discussionsupporting
confidence: 78%
“…MT hyperdynamicity, along with deficits in slow axonal transport, has also been measured in a model of amyotrophic lateral sclerosis with this stable isotope-labeling technique (Fanara et al, 2007). No changes in total tubulin or MTs are observed, demonstrating another neurodegeneration model where in vivo changes in MT turnover would not have been detected without stable isotope labeling.…”
Section: Discussionmentioning
confidence: 96%
“…Altered MT dynamics in tau transgenic mice MT dynamics can be measured in vivo using a novel deuterium labeling procedure (Fanara et al, 2004(Fanara et al, , 2007(Fanara et al, , 2010. Following labeling of body fluids with 2 H 2 O, deuterium becomes incorporated into nonessential amino acids and then into newly synthesized proteins.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…8), including competition for dynein transport, disruption of dynein motor activity, physical blockage of dynein transport by mutant SOD1 aggregates, and destabilization of microtubules. A recent study showed that microtubule destabilization is an early event in ALS, and a microtubule stabilization drug had beneficial effects in ALS mice (53). Reduced number of available microtubule tracks in combination with increased levels of misfolded mutant SOD1 bound to dynein could over time lead to severe reduction of transport of other cargos such as neurotrophic factors necessary to promote neuronal survival, thus causing neurotoxicity.…”
Section: Discussionmentioning
confidence: 99%